Children's Rights and Resistance to Hegemony in the Lebanese Film Capernaum by Nadine Labaki - Nugraha, Reza Sukma; Farhah, Eva; Arifuddin, Arifuddin (Arabi : Journal of Arabic Studies, 2024)
Nadine Labaki's Capernaum represents the impact of poverty on the fulfillment of children's rights. In this article, the issue of poverty and its social consequences are analyzed through the story of the main character Zain, a street child who struggles with all forms of poverty in Lebanon. Using Gramsci's theory of hegemony, the research reveals how poverty, as a form of economic hegemony, affects children's lives and how they resist these conditions in their capacity as children. The analysis focuses on the representation of poverty and its influence on the fulfillment of children's rights, especially the rights to survival, protection, development, and participation. The research findings show that the film creates awareness of social issues, such as poverty and children's rights, and encourages children as members of society to take concrete actions against the hegemony. It is also a critique of the power that overrides children's rights and considers children as passive objects in society.